Exercise and hypoxia-induced hypercoagulability is counterbalanced in women in part by decreased platelet reactivity - Ninivaggi, M.; Swieringa, F.; Middelveld, H.; Schmalschläger, V.; Roest, M.; de Laat-Kremers, R.; de Laat, B. (Thrombosis research, 2024)
Hypoxia plays an important role in several pathologies, e.g. chronic obstructive pulmonary disease and obstructive sleep apnea syndrome, and is linked to an increased thrombosis risk. Furthermore, oxygen deprivation is associated with hypercoagulability. In this study, we investigated the effect of gender and exercise on the coagulation potential under hypoxic conditions at high altitude by assessing thrombin generation (TG) and platelet activation. Hereto, ten healthy volunteers were included (50 % male, median age of 27.5 years). The measurements were conducted first at sea level and then twice at high altitude (3883 m), first after a passive ascent by cable car and second after an active ascent by a mountain hike. As expected, both the passive and active ascent resulted in a decreased oxygen saturation and an increased heart rate at high altitude. Acute mountain sickness symptoms were observed independently of the ascent method. After the active ascent, platelet, white blood cell and granulocyte count were increased, and lymphocytes were decreased, without a gender-related difference. FVIII and von Willebrand factor were significantly increased after the active ascent for both men and women. Platelet activation was reduced and delayed under hypobaric conditions, especially in women. TG analysis showed a prothrombotic trend at high altitude, especially after the active ascent. Women had a hypercoagulable phenotype, compared to men at all 3 timepoints, indicated by a higher peak height and endogenous thrombin potential (ETP), and shorter lag time and time-to-peak. In addition, ETP and peak inhibition by thrombomodulin was lower in women after the active ascent, compared to men. Interestingly, data normalisation for subject baseline values indicated an opposing effect of altitude-induced hypoxia on α2-macroglobulin levels and TG lag time between men and women, decreasing in men and increasing in women. We conclude that hypoxia increases TG, as well as FVIII and VWF levels in combination with exercise. In contrast, platelets lose their responsiveness at high altitude, which is most pronounced after heavy exercise. Women had a more pronounced prothrombotic phenotype compared to men, which we theorize is counterbalanced under hypobaric conditions by decreased platelet activation. •Hypoxia in combination with exercise increased thrombin generation, FVIII and VWF•Platelets lost responsiveness at high altitude, especially after heavy exercise•Women had a more pronounced prothrombotic phenotype compared to men